'Extravagant and reckless' wives and indebted husbands: examining the equity of exoneration. Issue 5 (20th April 2018) - Jackson, Abigail
Abstract: In Armstrong v Onyearu, the Court of Appeal considered the equity of exoneration and, in particular, whether it would apply in circumstances where the wife had received an indirect benefit from the loan. Reflecting on that judgment, this article examines the nature of the equity of exoneration, its legal basis and the economic, social, and political context in which it operates. It will conclude that, while the equity of exoneration may offer some protection to a surety wife, it favours women who are financially independent, as opposed to those who stay at home or support their husbands in business.